1986
DOI: 10.1136/pgmj.62.732.925
|View full text |Cite
|
Sign up to set email alerts
|

Rational preoperative evaluation

Abstract: Summary:Clinical data from two hundred consecutive patients undergoing surgical procedures at the Salt Lake City VA Hospital form the basis of this study. Results of nine commonly ordered preoperative tests (blood count, differential, electrolytes, chemistry panel, urinalysis, prothrombin time, partial thromboplastin time, electrocardiogram, and chest X-ray) were matched with the preoperative history and physical examination and the outcome of surgery in each patient. Each test was examined by (1) the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…Based on the evidence, the practice of indiscriminate coagulation testing is not justifiable, at least for the population of preoperative patients included in this systematic review. Although some defend it as a means of avoiding litigation, it has been demonstrated that 30–95% of unexpected laboratory results from screening tests are either not documented or not pursued further (Muskett & McGreevy, 1986; Johnson & Mortimer, 2002). Therefore, random screening could potentially increase rather than reduce the risk of litigation.…”
Section: Predictive Value Of Coagulation Screening Testsmentioning
confidence: 99%
“…Based on the evidence, the practice of indiscriminate coagulation testing is not justifiable, at least for the population of preoperative patients included in this systematic review. Although some defend it as a means of avoiding litigation, it has been demonstrated that 30–95% of unexpected laboratory results from screening tests are either not documented or not pursued further (Muskett & McGreevy, 1986; Johnson & Mortimer, 2002). Therefore, random screening could potentially increase rather than reduce the risk of litigation.…”
Section: Predictive Value Of Coagulation Screening Testsmentioning
confidence: 99%
“…Eleven studies were in adults, 18,20,21,23,33,[36][37][38]40,45,46 four of the studies were in children, 28,[30][31][32] four were in both adults and children, 27,41,44,47 and in the remainder of the studies the age of the study population was not specified. 24,26,29,34,35,39,42,43,48 Of the 28 studies, all measured abnormality rates, 18 measured impact on clinical management, 18,20,21,27,28,[30][31][32]34,35,[37][38][39][40]42,45,47,48 and six measured the number of relevant adverse events (for example, respiratory complications) in patients with an abnormal test finding. 20,23,…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…Several reports have also considered whether the information obtained from routine preoperative radiographs have had or might have had, any influence on health outcomes. 15,[17][18][19]29 Since this test, when carded out on large numbers of patients, is associated with considerable costs and some health effects, it is important to establish the frequency with which new information of.clinical value is obtained, The present report describes a meta-analysis of published studies and was carried out with the object of estimating this frequency with greater confidence than could be derived from any individual report on its own. Unfortunate.ly, there is insufficient evidence on which to base estimates of how frequently information resulting from routine radiography influences health outcomes.…”
Section: Sont Indus Clans La M~ta-analyse En Moyenne Des Anomalies mentioning
confidence: 99%